Proximal Contact Points between Fixed Dental Restorations during Bisque Trial Stage - Khanal, Bibek; Mishra Sapkota, Srijana; Thakur, Smriti N; Chaulagain, Rajib; Adhikari, Bhawana (Journal of Institute of Medicine Nepal, 2022)
Introduction: Proper proximal contact points between a crown and adjacent teeth plays an important role in the gingival health and longevity of the prosthesis. This study was conducted to assess the proximal contact points between a metal ceramic crown and adjacent teeth in bisque trial stage. Methods: A cross-sectional study was conducted in a total of 75 maxillary and mandibular 1st molar crowns to assess the type of contact points present on the mesial and distal side by using a dental floss. The contact points were categorized as being either open, acceptable or too tight. Descriptive statistical analysis (frequency and percentage) was done using SPSS Software (version 21.0). Results: In this study 75 crowns were studied to assess the proximal contact points in 150 (75 mesial and 75 distal) sites. A total of 24 (16%) sites showed open contact points, 47 (31.33%) showed acceptable contact points and 79 (52.66%) sites showed too tight contact points. Conclusion: A significant number of crowns showed open and too tight type of contact points. These can be rectified before final cementation since the assessment was done during the bisque trial stage.